Analisis Pengaruh Penambahan Kaolin Sebagai Subtitusi Semen Terhadap Kuat Tekan Beton Ringan - Febryandi Febryandi; Debby Sinta Devi; Rahmad Roni Julio; Adelia Cristine (Jurnal Tekno Global, 2022)
Concrete is a very important construction material and has good compressive properties. According to its mass, concrete is divided into ordinary concrete and lightweight concrete. Light weight concrete is 1000-2000 kg/m3. In high construction projects the use of lightweight concrete can reduce the mass of the building itself. The latest innovation in lightweight concrete is the addition of kaolin as a cement substitute. Kaolin is a clay or clay mineral that contains a lot of aluminum silica. Stryofoam is one of the materials that can be used in lightweight concrete mixes. The use of kaolin and styrofoam waste is sought to support construction materials that are more environmentally friendly. The purpose of this study was to determine the effect of the addition of kaolin on compressive strength so that it can be used as an admixture in lightweight concrete. The results showed that the weight of concrete mixed with 5%, 10%, 15% kaolin and 60% Styrofoam at the age of 28 days was 1836 kg/m³, 1845 kg/m³, 1852 kg/m³. The average compressive strength for the kaolin variants 5%, 10%, 15% were 8.28 MPa, 8.46 MPa, 10.11 MPa. Based on this it was concluded that concrete using a mixture of kaolin and 60% stryofoam can be used in light construction. Because the weight of the lightweight concrete tested was lower than normal concrete and met the specified requirements, namely the specific gravity of the resulting concrete was in the range of 1000-2000 kg/m³.